Literatura e Emoções: A função hermenêutica dos afetos - Leonor Simas-Almeida (Investigação, 2019)
This is a collection of heterogeneous essays referred to literature from diverse periods and nationalities. They were put together for the main purpose of illustrating a variety of possibilities regarding a kind of literary analysis based on the hermeneutical power of affect and emotions in art. The volume is divided into two major sections. The first one contains essays on novels where female protagonists play a central role, whereas the second consists of studies exploring other types of narrative devices, also concerned with the construction of emotions, taken as powerful vehicles of meaning in the readings there proposed.